The analysis of work characteristics leading to high job satisfaction in Romania - Kerekes, Kinga; Zaharie, Monica Aniela; Rațiu, Patricia Iulia (Anali Ekonomskog fakulteta u Subotici, 2023)
Job satisfaction is one of the most analyzed job attitudes which may have significant positive consequences on the individual-level and organizational-level performances, too. This is why companies have to analyze the antecedents of job satisfaction. Work design and work characteristics have compelling impact on employees’ job satisfaction. The aim of this paper is to identify the work characteristics with the highest impact on job satisfaction across various occupations and positions in Romania. The empirical research had been carried out within the Global Work Design Project initiated by the Academy of Management HR Division, based on the work design questionnaire (WDQ) developed by Morgeson and Humphrey (2006). The Romanian sample consisted of 394 employees from 69 organizations. In our paper we identify the job features and characteristics which lead to high job satisfaction. The findings may have empirical implications on companies’ HR strategies not only in Romania, but also in other countries from the Central and Eastern European region.